2018
DOI: 10.1038/s41467-018-05168-7
|View full text |Cite
|
Sign up to set email alerts
|

A TRAF3-NIK module differentially regulates DNA vs RNA pathways in innate immune signaling

Abstract: Detection of viral genomes by the innate immune system elicits an antiviral gene program mediated by type I interferons (IFNs). While viral RNA and DNA species induce IFN via separate pathways, the mechanisms by which these pathways are differentially modulated are unknown. Here we show that the positive regulator of IFN in the RNA pathway, TRAF3, has an inhibitory function in the DNA pathway. Loss of TRAF3 coincides with increased expression of the alternative NF-κB-inducing molecule, NIK, which interacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 70 publications
(87 reference statements)
5
30
0
Order By: Relevance
“…A recent study suggests that TRAF3 negatively regulates DNA virus-induced type I IFN induction with a mechanism that involves STING activation by the TRAF3-controlled kinase NIK [17]. Consistent with this report, we found that the TRAF3-deficient MEFs had greatly enhanced type I IFN induction by a DNA virus, herpes simplex virus 1 (HSV-1) (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A recent study suggests that TRAF3 negatively regulates DNA virus-induced type I IFN induction with a mechanism that involves STING activation by the TRAF3-controlled kinase NIK [17]. Consistent with this report, we found that the TRAF3-deficient MEFs had greatly enhanced type I IFN induction by a DNA virus, herpes simplex virus 1 (HSV-1) (Fig.…”
Section: Resultssupporting
confidence: 91%
“…A recent study suggests that TRAF3 negatively regulates type I IFN induction by DNA viruses, such as HSV-1, through controlling the noncanonical NF-κB inducing kinase NIK [17]. Accumulation of NIK due to TRAF3 deficiency promotes STING activation and induction of type I IFNs [17]. In support of this report, we found that TRAF3 deletion in MEFs and macrophages promotes HSV-1-stimulated expression of Ifna and Ifnb genes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…RELB is a proto-oncogene comprising one of the NF-kB subunit. After phosphorylated p100 is degraded by the proteasome to p52, p52 and REBL form into a heterodimer to elicit non-canonical NF-κB signals [32,33]. Interestingly, the production of canonical NF-κB signals resembles that of non-canonical one.…”
Section: Cgas-sting-mediated Molecular Changesmentioning
confidence: 99%
“…The ndings suggest that Parkin plays a novel role in innate immune signaling by targeting TRAF3 for degradation and maintaining the balance of innate antiviral immunity [50]. A TRAF3-NIK axis differentially regulates viral DNA vs RNA pathways in innate immune signaling [51]. KLC1 encodes a member of the kinesin light chain family.…”
Section: Role Of Candidate Genesmentioning
confidence: 99%